Informalidade, educação e tecnologias digitais: um estudo sobre o trabalho dos motoristas da empresa Uber na cidade de Uberlândia-MG - Oliveira, Luciene Correia Santos de (2023)
Approaching the topic of uberized work in contemporary society, this thesis was developed along with the line of research “Work, Society and Education”, of the Postgraduate Program in Education at Federal University of Uberlândia (UFU, in Portuguese abbreviation). In the Information Age, forms of online and digital work, the service sector and informality have expanded – the precariousness, intensification and instability are significant traits. In this scenario, the uberization of work has gained ground and developed in contemporary society, which is based on neoliberal values and structural unemployment. The ideas of sharing economy and entrepreneurship have obtained strength and encouraged free initiative and self-employment. Characterized by its pioneering and popularization, the performance of the company Uber exposes contradictions in the world of work. Based on these assumptions, this investigation aimed to analyze the work of Uber app drivers in the city of Uberlândia, Minas Gerais, Brazil, reflecting on informal digital work and education, especially concerning the school and professional training of these workers and the uberization process in which they are immersed. For this purpose, a case study was carried out in order to critically analyze the relationship between work and education among app drivers and question the directions in which this aspect has been trodden, which are associated with precarious conditions and the increasingly complex and contradictory role of digital technologies and capital. The problematization of this research took place under the inspiration of dialectical and qualitative approaches in an exploratory research with bibliographic review studies and field research. Twenty app drivers linked to the company Uber and working in the referred city answered the electronic questionnaire with questions about their profile, relationship with work and school and/or professional training, in addition to motivations and perspectives on uberized work. These data, as well as the theoretical and conceptual framework discussed throughout the sections, were important to problematize the role of digital technologies as work tools; informal work and the uberization process; the profile of uberized workers; the precariousness and intensification of work and the training of workers. Throughout this research, the thesis defended that uberization has been constituted in a growing, effective and still ongoing process, at the apex of the exploration process in contemporary times by making use of technologies, digital work and the training of workers in its favor. It is a diffuse exploration that captures their capacities for manual and intellectual work, placing in their hands all the responsibility of work with the influence of neoliberal values that govern social life and the perspectives and ideals of workers in contemporary times and manages to lead the working class, whether believing that it is undertaking, or due to the lack of other opportunities, to opt for precarious work. Literate (or not) workers are submitted to the ideological domain and moved by the needs of survival in a process that, contradictorily, homogenizes them even though they are clearly a heterogeneous group endowed with needs, desires and particularities ignored in favor of the interests of capital.